PEMBELAJARAN SEJARAH DI SEKOLAH: DARI PRAGMATIS KE IDEALIS - Joko Sayono (Jurnal Sejarah dan Budaya, 2013)
Abstract. Teaching of history has been conducted by bad images for along time. The images of history teaching are as recalling, not interesting, unpleasant, and boring lesson. Based on reasoning of urgent role of history lesson as nation character building for students, there is need to change this condition. Mind set of teacher as responsible actor has to be changed from pragmatic to idealist paradigm. History teaching process has to be shifted form the orientation of curriculum material finishing to the real goal attainment, that is the arising of historical consciousness for students.